2018
DOI: 10.1371/journal.pone.0193646
|View full text |Cite
|
Sign up to set email alerts
|

Current Helicobacter pylori infection is significantly associated with subclinical coronary atherosclerosis in healthy subjects: A cross-sectional study

Abstract: Helicobacter pylori is a gastrointestinal pathogen known to be associated with cardiovascular disease (CVD). However, most analyses about the effect of H. pylori infection have been done in patients with a history of CVD but not in healthy subjects. We evaluated the association between H. pylori infection and subclinical atherosclerosis by using cardiac multidetector computed tomography (MDCT) in healthy subjects without previous CVD. From December 2007 to February 2014, 463 subjects who underwent the rapid ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 60 publications
2
57
0
8
Order By: Relevance
“…Interestingly, arterial hypertension and renal disease were significantly associated with the absence of H. pylori eradication. Another study by Lee et al 3…”
Section: Ard I Ova Scul Ar D Is E a S E Smentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, arterial hypertension and renal disease were significantly associated with the absence of H. pylori eradication. Another study by Lee et al 3…”
Section: Ard I Ova Scul Ar D Is E a S E Smentioning
confidence: 96%
“…Interestingly, arterial hypertension and renal disease were significantly associated with the absence of H. pylori eradication. Another study by Lee et al tested the association between H. pylori infection and subclinical atherosclerosis, using a multidetector computed tomography (MDTC) in subjects without previous history of cardiovascular diseases (CVD). They enrolled 463 subjects who underwent upper GI endoscopy with rapid urease test (CLO test), pulse wave velocity (PWV) measurement, and MDCT.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…In China, the infection rate of H. pylori is 40%-60% (Chen et al, 2019). In recent years, in addition to its role in gastrointestinal diseases, several nongastric issues have been found to have a close relationship with H. pylori infection (Adachi et al, 2018;Yong and Upala, 2018;Lee et al, 2018). H. pylori treatment relies on a combination of antimicrobial agents, such as amoxicillin, clarithromycin, metronidazole, and antisecretory agents, such as proton pump inhibitors (PPIs) (Yang and Lu, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A number of immunological and experimental studies have demonstrated the importance of inflammation in the initiation and progression of atherosclerosis, including the final thrombotic occlusion (1,2). Considerable evidence has emerged that this inflammatory process is sustained, at least in part, by bacteria or viruses, particularly Chlamydia pneumoniae (3), H. pylori (4,5), and Cytomegalovirus (6). It has been proposed that the effect of infection on the vascular wall may be direct, or indirect, by inducing an autoimmune inflammatory response (7).…”
Section: Introductionmentioning
confidence: 99%
“…Although the published data so far are not entirely concordant, recent analysis of previous studies have provided convincing evidence of a possible role of H. pylori (21,22). Recent studies have also demonstrated a trend toward a decrease in the occurrence of CHD after H. pylori eradication (23) and association between H. pylori infection with subclinical significant coronary artery stenosis in a healthy population (5).…”
Section: Introductionmentioning
confidence: 99%